A 3‐Day Randomized Clinical Trial to Investigate the Desensitizing Properties of Three Dentifrices. Issue 11 (1st November 2013) - Orsini, Giovanna; Procaccini, Maurizio; Manzoli, Lamberto; Sparabombe, Scilla; Tiriduzzi, Paolo; Bambini, Fabrizio; Putignano, Angelo
Abstract : Background: The aim of the present study is to evaluate the relative abilities of three desensitizing dentifrices to provide rapid relief of dentin hypersensitivity (DH). Methods: Using a double‐mask, randomized design, three dentifrices: 1) containing 8% arginine and 1, 450 ppm sodium monofluorophosphate; 2) containing 8% strontium acetate and 1, 040 ppm sodium fluoride; and 3) containing 30% microaggregation of zinc‐carbonate hydroxyapatite nanocrystals were compared after 3‐day treatment. Participant's DH was evaluated at baseline and after 3 days using air‐blast, tactile, cold water, and subjective tests. Results: The final sample consisted of 85 individuals: 29 received the arginine‐based dentifrice (group 1), 27 the strontium acetate–based dentifrice (group 2), and 29 the dentifrice based on zinc‐carbonate hydroxyapatite (group 3). All dentifrices were mostly effective to reduce DH: the percentage of score reduction from baseline to 3 days was >30% for all tests (except for subjective test of group 2). The comparison among the three dentifrices showed that, after 3 days, there was an improvement in air‐blast (mean percentage of reduction, 39.2% in group 1, 42.0% in group 2, and 39.2% in group 3), cold water (41.5%, 51.8%, and 50%), tactile (50.3%, 40.1%, and 33.8%), and subjective (33.1%, 17.4%, and 31.4%) test scores, with differences being significant for cold water and subjective tests. For air‐blast and tactile tests, there were no significant differences across groups at 3 days. Moreover, no significant differences at any test were observed in a subset of patients that were followed up to 8 weeks: all dentifrices were all highly efficacious. Conclusions: This study documents that the three tested dentifrices significantly reduced DH after 3‐day treatment, supporting their use in clinical practice. To the best of the authors' knowledge, this is the first report documenting the rapid relief from DH of a zinc‐carbonate hydroxyapatite dentifrice.